Predisposing genes and increased chromosome aberrations in lung cancer cigarette smokers - ConfortiFroes, N.; ElZein, R.; AbdelRahman, S. Z.; Zwischenberger, J. B.; Au, W. W. (Elsevier B.V., 1997)
Genotoxic effects linking cigarette smoking with lung cancer have not been consistently demonstrated, therefore claims for the cause-effect relationships are vigorously contested. Using matched populations of 22 lung cancer patients who have been cigarette smokers (LCP), 22 non-cancerous cigarette smokers (SC) and 13 non-smokers (NSC), we have applied the fluorescence in situ hybridization (FISH) tandem probe assay to elucidate the frequency of chromosome breakage among the participants. Two probes were used, a classical satellite probe which hybridizes to the large heterochromatin region of chromosome 1, and an alpha-satellite probe which targets a small region adjacent to the heterochromatin probe. The highest frequency of structural aberrations was observed in LCP (1.4 +/- 0.1) followed by SC (1.25 +/- 0.1) and NSC (0.4 +/- 0.1). Aberration frequencies were not significantly different between LCP and SC (p > 0.05), however, a statistically significant difference was detected between the smoker populations combined (LCP and SC) and the NSC (p < 0.001). The breakage frequencies showed a positive correlation with duration of smoking for LCP (r = 0.5; p < 0.01), but not for SC (P > 0.05). In addition, the aberration frequencies were influenced by the inheritance of polymorphic glutathione S-transferase (GST) genes. LCPs missing one or the other GST (GSTM1 or GSTT1) genes were found to have significantly higher chromosome breaks compared to LCPs with both genes present (p < 0.05), Our data indicate that genetic predisposition and chromosome aberrations may be mechanistically related to the initiation of lung carcinogenesis; therefore, they may be useful biomarkers for lung cancer among cigarette smokers. (C) 1997 Elsevier B.V. B.V.
Keywords: chromosome aberration; polymorphic GST gene; lung cancer; cigarette smoker